Socialization Of Selection Of Gonggong Shell And Shell Waste As Materials For Handcrafts In Serip Mangrove Village - Gunawan, Agung Arif; Silitonga, Frangky; Atmaja, Hari Sandi; Rini, Rosie Oktavia Puspita (JURNAL KEKER WISATA, 2025)
This community service activity aims to provide education and training to the people of Kampung Tua Bakau Serip regarding the utilization of gonggong and clam shell waste as basic materials for handicrafts. This abundant but not optimally utilized marine waste has high economic potential if processed with the right techniques. The method of implementing the activity includes socialization, demonstration of making crafts, and technical assistance. The results of this activity show an increase in community knowledge and skills in processing shell waste into products with sales value such as wall hangings, key chains, and home accessories. This activity also opens up new business opportunities that can support the local economy and preserve the environment.